Perbedaan Pengaruh Terapi Psikoreligius dengan Terapi Musik Klasik terhadap Kecemasan Pasien Pre Operatif di RSUD dr. H. Abdul Moeloek Provinsi Lampung - El Rahmayati; Ririn Sri Handayani (Jurnal Kesehatan, 2017)
The surgical procedure for most patients triggers anxiety and fear. Approximately 60-80% of patients who will undergo surgery experience anxiety that needs to be intervened in the category of moderate to severe anxiety (Efendy, 2005 in Faradisi, 2012). This study aims to determine the effect of psycho-religious therapy and classical music therapy on pre operative patient anxiety in RSUDAM Lampung Province in 2016. This research type is quasi-experiment research with non-equivalent control group design. This research was conducted at RSUDAM Lampung Province in September- November 2016 in three surgical wards: the gelatik room (orthopedic surgery), the kutilang room (male general surgery) and the rose room (female general surgery). The population taken were all pre operative patients within the study period. The sampling technique uses a purposive method and the sample size is 80 people divided into 2 groups ie the group which is given the classical music intervention and the group that is given psycho-religious therapy with religious music and murrotal Al Quran surah Arrahman. The data were collected using a survey of Zung Self Anxiety Rating Scale (ZSARS) instruments before and after treatment. Bivariate analysis was performed using independent t-test statistic test by setting Alpha value 0,05 and 95% CI. The results of this study conclude that there are differences of psycho-religious therapy and classical music therapy on pre operative patient's anxiety at RSUDAM Lampung Province 2016 (p-value 0,030) with a decrease of ZSARS score in patients treated with psycho-religious therapy 2,250. Researchers suggested that psycho-religious therapy performed on pre operative patients at RSUDAM Lampung Province and entered into one form of intervention to decrease preoperative anxiety.